INTEGRATING ISLAMIC ENVIRONMENTAL ETHICS, STATE REGULATORY SYSTEMS, AND BEHAVIORAL GOVERNANCE TO STRENGTHEN WASTE MANAGEMENT PRACTICES - Nur Kholis (At-Thullab : Jurnal Mahasiswa Studi Islam, 2026)
This study examines poor waste management as an environmental, ethical, and governance challenge by integrating insights from Islamic jurisprudence, state regulations, and behavioral governance. The aim is to explain how ecological degradation arises from human behavior that contradicts religious principles and formal waste management laws, and to propose a conceptual model linking ethical norms to regulatory mechanisms and behavior. Using a qualitative conceptual methodology, the study analyzes scriptural sources, classical jurisprudential reasoning, national waste regulations, and descriptive evidence of environmental conditions to build an interdisciplinary understanding of this issue. The results show that Islamic jurisprudence establishes clear prohibitions against actions that result in environmental damage, framing waste pollution as a violation of ethical and legal obligations. National regulations also mandate responsible waste management practices, yet poor management persists because behavioral changes have not aligned with legal expectations. This analysis highlights the central role of human behavior as a determining factor in waste governance, illustrating how religious education, societal norms, and institutional policies shape or hinder responsible practices. The integrated model developed in this study demonstrates that effective waste governance requires the convergence of moral awareness, legal enforcement, and behavioral adaptation. This study concludes that sustainable environmental management in a Muslim-majority context depends on aligning internal ethical motivations with external regulatory frameworks. This conceptual integration offers a foundation for future empirical research and suggests new pathways for policy design, community engagement, and faith-based environmental education